Collaborative Learning Design: An Innovation through Sharing and Jumping Tasks - Rr. Eko Susetyarini; Sri Wahyuni; Roimil Latifa; Cantia Putri; Fuad Jaya Miharja (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
The article aims to implement collaborative learning through innovative sharing and jumping tasks. This qualitative descriptive research was conducted at Junior High School 8 of Muhammadiyah Batu from July to December 2019. The research was conducted in grade VII involving nine observers. Learning activities were carried out in two open classes with a cycle of planning, implementing, and evaluating. Collecting data used observation sheets, questionnaires, and learning implementation sheets. Data analysis was performed using the Miles and Huberman model. The results showed that teacher learning assistance in collaborative learning design with sharing task innovation and jumping task facilitates students' critical thinking and communication skills. It can be observed in two open classes and strengthened by the end of each stage's evaluation results. This study recommends teachers in designing collaborative learning with innovative designs of sharing tasks and jumping tasks. Keywords: Collaborative Learning, Jumping Task, Sharing Task